Nikmat Sesaat Mengurangi Kesadaran Hidup di Hari Kelak (Analisis Penafsiran Qs. At-Takatsur dalam Tafsir Al-Azhar) - Saiful Bakri; Umi Wasilatul Firdausiyah (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2023)
This study aims to examine and analyze the meaning of favors contained in Surah At-Takatsur by analyzing Al-Azhar's interpretation. The method used in this research is qualitative literature research with the descriptive-analytical method, assisted by Hans George Gadamer’s horizon theory as a bridge to reveal favors in Surah At-Takatsur in the interpretation of Al-Azhar. This study showed that: 1) the favors described in the surah are related to the favors of this mortal world, 2) The favors obtained by humans can be neglected in life in the future, and these favors will be accounted for in the future, 3) The true pleasure is the enjoyment of life in the future.